The English language needs of nurses in medical tourism in Malaysia / Aditya Karuthan - Karuthan, Aditya (2015)
Good English Language communication skills are very important for nurses as they are service providers to patients and deal with doctors, medical support staff and relatives of patients. This study looks at the English language communicative challenges and needs faced by nurses engaged in Medical Tourism in Malaysia. The objectives of this study are to identify: 1) the English Language communicative challenges of these nurses, 2) the English Language communicative needs of these nurses and 3) the language skills required in a proposed English Language curriculum for the nurses. This study uses the concurrent triangulation strategy using quantitative and qualitative approaches to cross validate, corroborate the findings and to complement the weakness and strengths of the two methods (Creswell, 2009). The quantitative section was a questionnaire developed based on instruments used by Basturkmen (2010), O’ Neil (2011) and Wang et al. (2008) and supplemented exploratory interviews with nurses and nursing tutors on communication issues by these nurses. 128 questionnaires from 4 hospitals were collected and analysed using SPSS. In the qualitative section, semi-structured interviews on self-evaluation, problems faced, experiences encountered and recommendations were conducted. Fourteen nurses, two human resource managers, two matrons, two sisters, one clinical instructor participated in the study. Preliminary analysis was based on categories obtained from the quantitative data such as problems encountered, coping strategies and communication situations. The preliminary analysis was then developed into thematic analysis. The results of the first research question revealed that the majority of the nurses especially the new, junior nurses faced problems understanding spoken English and had difficulty speaking in English. Nurses cited different accents, slangs, idiomatic phrases and rapid pace of spoken English made it difficult to understand patients. These nurses’ use of Basic English, at times sounding curt and rude did not aid in building rapport with patients. The findings indicated that nurses faced problems in reading and writing nursing documents in English. Often grammar, spelling mistakes, code-switching and use of Manglish were observed. Use of Malay, was common. Interestingly, Malaysian nurses often resorted to getting help from other proficient nurses when encountered with English communication problems. The findings revealed, almost all the nurses wanted to improve their English language skills and were interested in enrolling for a two to three hour class per week. The needs of the nurses include improving general proficiency of the language, focusing on all four skills, grammar and medical vocabulary. From the interviews, recommendations such as being exposed to authentic work–related situations and reviewing previous written reports and appointing a clinical instructor to help new nurses were made. Based on the findings, a three hour, 12 weekly, intermediate course for nurses in the medical tourism sector was developed. The activities in the proposed curriculum are learned-centred as this will allow students to practice, reinforce and explore the language for themselves in work–related situations. The findings of this research have pedagogical implications especially for current nursing programs.